The influence of perceived organizational support (POS), perceived supervisory support (PSS) and organizational commitment (OC) towards intention to leave or intention to stay: a case of casual dining restaurants in Klang Valley, Malaysia - Ghazali, Hazrina; Mohamad Nashuki, Nasyira; Othman, Mohhidin (Human Resource Management Academic Research Society, 2018)
Restaurant industry in Malaysia is continuing to grow positively and considered as one of sector that deal with number of employees. Due to this scenario, it can be said that managing employees in this industry very challenging especially in retaining them. Employees may quit due to many reasons. Hence, the management needs to monitor their employees before they have the intention to leave the organization. This study aims to examine the relationship between perceived organizational support (POS), perceived supervisor support (PSS), and organizational commitment (OC) and employees’ intention to leave or stay in the casual dining restaurant in Klang Valley area. A total of 855 questionnaires have been distributed among employees working in the casual dining restaurant in Klang Valley area. This study employed convenient sampling and a total of 717 usable questionnaires gathered which gave an 84% response rate. This study was analyzed by using structural equation modeling and results from research findings indicated that organizational commitment (OC) was found to be the most influential for both intention to leave β = -0.31 (p < 0.001) and intention to stay β = 0.75, p < 0.001. The finding is expected to help management to highlight this factor and plan strategies to retain their staff and minimize actual turnover from occur.